195k views
1 vote
Function rule to find f(–11).

Function rule to find f(–11).-example-1

2 Answers

4 votes

Answer:

-16

Explanation:

Given that,

f ( x ) = x - 5

To find the value of f ( -11 ), you have to replace x with -11 & solve it.

Let us solve it now.

f ( -11 ) = x - 5

f ( -11 ) = -11 - 5

f ( -11 ) = -16

User Nmakb
by
5.1k points
2 votes

Answer:

f(-11) = -16

Explanation:

We are given a function

f(x) = x-5

Substitute the value of x = -11 into the function

f(-11) = -11-5

= -16

User Martinjlowm
by
5.2k points